KNOWLEDGE AND AWARENESS OF HUMAN PAPILLOMAVIRUS (HPV), CERVICAL CANCER AND HPV VACCINES AMONG MEDICAL STUDENTS - VIKRANT C. SANGAR; DR. B. B. GHONGANE (International Journal of Pharma and Bio Sciences, 2013)
Cervical cancer is one of the leading causes of morbidity and mortality among the gynaecological cancer worldwide. Medical students should be aware of cervical cancer, Human Papillomavirus and Human Papillomavirus vaccines. Therefore, to assess the status of knowledge and awareness of cervical cancer, human papillomavirus and human papillomavirus vaccines among them a cross-sectional, questionnaire based survey was conducted in preclinical (Group I, 129), paraclinical (Group II, 148) and clinical level (Group III, 78) medical students. The data was analyzed using Microsoft Access and Excel software. Preclinical Group had least knowledge. Paraclinical Group was unaware regarding Human Papillomavirus vaccines pricing (58.97%), vaccine manufacturer (81%) and dosing schedule (81%). Clinical Group is unaware of Human Papillomavirus vaccines availability (50%), vaccine dosing schedule (57.65%), manufacturers (65%) and vaccine preparation technology (79.48%). Therefore, there is a need to educate them in these areas because in future they are going to play a pivotal role of physician.